Immunoregulatory Cells in Myasthenia Gravis - Wu, Ying; Luo, Jie; Garden, Oliver A. (Frontiers in Neurology, 2020)
Myasthenia gravis (MG) is a T cell-dependent, B-cell mediated autoimmune disease caused by antibodies against the nicotinic acetylcholine receptor or other components of the postsynaptic muscle endplate at the neuromuscular junction. Detections of these specific antibodies serve as excellent biomarkers for diagnosis, but do not adequately substitute for clinical evaluations to predict disease severity or treatment response. Several immunoregulatory cell populations are implicated in the pathogenesis of MG. The immunophenotype of these populations has been well-characterized in human peripheral blood. CD4+FoxP3+ regulatory T cells (Tregs) are functionally defective in MG, but there is a lack of consensus on whether they show numerical perturbations. Myeloid-derived suppressor cells (MDSCs) have also been explored in the context of MG. Adoptive transfer of CD4+FoxP3+ Tregs or MDSCs suppresses ongoing experimental autoimmune MG (EAMG), a rodent model of MG, suggesting a protective role of both populations in this disease. The imbalance between follicular Tregs and follicular T helper cells was found in untreated MG patients, correlating with disease manifestations. There is an inverse correlation between the frequency of circulating IL-10producing B cells and clinical status in MG patients. Taken together, both functional and numerical defects in various populations of immunoregulatory cells in EAMG and human MG have been demonstrated, but how they relate to pathogenesis and whether these cells can serve as biomarkers of disease activity in humans deserve further exploration.